A multi-dimensional study to estimate the behaviour of the general public during COVID-19 pandemic - Chappidi, Suryaprakash Reddy; K. V., Surya Teja; D., Karthik; T., Anil Kumar; K., Ramya; G., Madhavi (International Journal of Research in Medical Sciences, 2023)
Background: The COVID-19 pandemic has had a significant impact on societies all over the world, leading to significant shifts in individual behavior as well as societal norms. The goal of this study was to provide an in-depth look at the many different aspects of public behavior during the COVID-19 pandemic. Methods: Demographic information, COVID-19 knowledge and awareness, prevention adherence, vaccination attitudes, and psychological well-being as a whole were all be gathered through the quantitative survey. The subjective meetings will give further bits of knowledge into the hidden inspirations, discernments, and difficulties faced by people in following general wellbeing rules. Results: To find patterns and correlations among the various variables, statistical methods like regression analysis, factor analysis, and clustering algorithms were used in the data analysis. The subjective information was investigated specifically, separating key topics and accounts that shed light on the subtleties of the public’s way of behaving during the pandemic. Conclusions: In the end, the goal of this multidimensional study was to help make decisions based on evidence and come up with plans to improve public health and lessen the impact of infectious disease outbreaks like COVID-19.